From Hegel to Marx : studies in the intellectual development of Karl Marx - Hook, Sidney (Ann Arbor : University of Michigan, 1971)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Marx, Karl; Hegel; filosofie